Polarization of the hard bremsstrahlung of the relativistic electrons in a crystal - Kasian, S.V.; Morokhovskii, V.L. (Вопросы атомной науки и техники, 2007)
Results of the polarization measurements of high energy bremsstrahlung in crystals are presented. For analysis of the photon polarization the asymmetry of the yields of the single p-meson photo-production on proton was used. The asymmetry of the yields of products of p-meson photo-production on the liquid-hydrogen target are presented for bremsstrahlung photons with energy Eγ = 700 MeV generated by electrons with energy Eₑ₋ = 800 MeV in the Si-crystal targets with thickness 120 µm and 30 µm. The properties of the high energy bremsstrahlung in crystals for the cases of electron beam orientations under the small angles respectively to the crystal axis (111) and plane (110) are investigated. Приведено дані вимірювання поляризації високоенергетичного гальмового випромінювання релятивістських электронів в кристалах. Для аналізу поляризації фотонів використана асимметрія виходу фотонародження p-мезонів на протоні. Приведено асиметрії виходів фотонародження p-мезонів гальмовими фотонами з енергією Eγ = 700 МеВ, які генеруються електронами з енегією Eₑ₋ = 800 МеВ в кристалічних мішенях Si з товщиною 120 та 30 мкм. Досліджено властивості високоенергетичного гальмового випромінювання в кристалах у випадках, коли пучок електронів ориєнтований під малим кутом відносно вісі кристалу (111) та площини кристалу (110). Приведены результаты измерения поляризации высокоэнергетичного тормозного излучения релятивистских электронов в кристаллах. Для анализа поляризации фотонов использована асимметрия выхода фоторождения p-мезонов на протоне. Приведены асимметрии выходов фоторождения p-мезонов тормозными фотонами с енергией Eγ = 700 МэВ, генерируемых электронами с энегией Eₑ₋ = 800 МэВ в кристаллических мишенях Si с толщинами 120 и 30 мкм. Исследованы свойства высокоенергетичного тормозного излучения в кристаллах в случаях, когда пучок электронов ориентирован под малым углом относительно оси кристалла (111) и плоскости кристалла (110).